Intention to use mobile payment - comprehensive perspectives of the theory of trying and cynicism - Chen C.-C. (E3S Web of Conferences, 2023)
This study adopts the investigation research method, collects sample data with questionnaires, and uses the AMOS-SEM to verify the measurement model and structural model. The results of this study show that, (1) the attitude toward success has positive and significant impact on the attitude toward adoption of mobile payment directly; (2) the attitude toward failure has negative and significant impact on the attitude toward adoption of mobile payment directly; (3) the attitude toward learning has positive and significant impact on the attitude toward adoption of mobile payment directly; (4) the attitude toward adoption has positive and significant impact on the intention to adopt of mobile payment directly; (5) the generalized self-confidence has positive and significant impact on the attitude toward success directly; (6) the generalized self-confidence has negative and significant impact on the attitude toward failure directly; (7) the generalized self-confidence has positive and significant impact on the attitude toward learning directly; (8) the Cynicism has negative and significant impact on the intention to adopt of mobile payment directly; (9) the cynicism has significant moderating effect between the attitude toward adoption and the intention to adopt. Finally, this study puts forward the corresponding theoretical and managerial implications based on the research results.